Страхование: учебное пособие / Ю. А. Сплетухов, Е. Ф. Дюжиков - Сплетухов Юрий Александрович (Высшее образование, 2008)
Экземпляры: аб. (2008) / Инвентарный номер: 52109 / Цена: / Сис.шифр: 65.271 / Авт.знак: С 72 / ГРНТИ: 06.73.65 / ББК: 65.271я73